The Development of Learning Media by Adobe CS6 Based on Contextual Teaching and Learning Approach on The Chapter Environmental Pollution - Rosita Fitrah Dewi; Nabila Risky Amalia (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2022)
The contextual approach to learning biology emphasizes understanding concepts related to phenomena that occurred around them. Moreover, environmental pollution material needs real examples to understand students about the material. This study aims to describe the process of development and validity of adobe flash CS6 professional-based learning media using a contextual teaching and learning (CTL) approach to environmental pollution material for class X at MAN 1 Pasuruan. This type of Research and Development (R&D) uses ADDIE model. The results of product validation from material experts, media experts, and biology teachers was 95.82%. This result indicates that the developed media is valid and could be used as a biology learning medium